Comparing intra-uterine injection of mononuclear cells and platelet-rich plasma on the pregnancy rate of women with recurrent implantation failure: An RCT - Hoda Fazaeli; Azar Sheikholeslami; Zahra Ebrahimi; Naser Kalhor; Leila Naserpour (International Journal of Reproductive BioMedicine)
Background: Recurrent implantation failure (RIF) can be explained mainly by improper crosstalk between the embryo and endometrium. The T-helper1/T-helper2 profile balance influences effective embryo implantation. Endometrial immunomodulation via intrauterine injection of activated peripheral blood mononuclear cells (PBMCs) or autologous platelet-rich plasma (PRP) is a potentially efficient treatment option.